Cubomedusae (Cubozoa, Carybdeida, Carukiidae) in Hong Kong, China: first records of cubozoans in Chinese waters confirmed using citizen science and digital authentication - John Terenzini; Sheldon Rey Boco; Laura J. Falkenberg (Check List, 2023)
The Hong Kong Jellyfish Project uses photographs and videos from citizen scientists to document the occurrence of jellyfish in this region. Based on these records, we describe sightings of two previously unrecorded species of box jellyfish, Malo filipina (Bentlage & Lewis, 2012) and an unidentified species of Morbakka sp. Gershwin, 2008, in Hong Kong Special Administrative Region, China. This understanding of where these species currently occur is important due to the potential impacts of box jellyfish on human activities and their role in local ecosystems.